Primary and Secondary Stability of Implants with Hydrophilic Surfaces in the Posterior Maxilla: A Split-Mouth Randomized Controlled Clinical Trial - Barbosa, Pablo Pádua; Cruvinel, Thales Martins; Sakakura, Celso Eduardo [UNESP]; de Oliveira, Guilherme José Pimentel Lopes; Zuza, Elizangela Cruvinel (Quintessence Publishing, 2021)
Purpose: The aim of this split-mouth randomized clinical trial was to evaluate the primary and secondary stability of implants with hydrophilic surfaces in comparison to implants with conventional surfaces in the posterior region of the maxilla. Materials and Methods: Twenty patients with a bilateral edentulous ridge in the posterior area of the maxilla randomly received implants with two types of surfaces: (1) implants with the surface modified by double acid-etching and sandblasting (DAS, n = 20); and (2) implants with the surface modified by double acid-etching and sandblasting, stored in 0.9% saline solution to confer highly hydrophilic properties (DAS-H, n = 20) on the surface. The implants presented the same macrostructure with a hybrid design. The resonance frequency analysis was performed in order to obtain the implant stability quotient (ISQ) using Osstell. The ISQ analyses were performed just after placement of the implant (primary stability) and at 28, 40, and 90 days after the surgical procedure (secondary stability). Results: There were no differences between the DAS and DAS-H surfaces in the primary stability or during the conversion of the primary to the secondary stability; however, there was a reduction in the stability of the implants at 28 days, which increased significantly at 40 and 90 days in both surfaces. Conclusion: It can be concluded that the surface wettability of implants with a hybrid macrostructure did not increase the primary and secondary implant stability in the posterior region of the maxilla
Keywords: dental implants; implant surface; stability